Influence of fault arc characteristics on the accuracy of digital fault locators. - Funabashi, T.
This paper proposes a time domain model of a fault locator with special reference to fault are nonlinearities by applying the MODELS language of the EMTP. It has been found that an impedance relay type locator is significantly influenced by the fault arc nonlinearities, while the current diversion ratio method is not influenced. This validates the advantage of the current diversion approach over the impedance approach
Keywords: EMTP; MODELS language; Computer simulation; Current diversion approach; Current diversion ratio method; Digital fault locator accuracy; Fault arc characteristics; Impedance relay type locator; Time domain model